Wath is this thing called happiness? - Feldman, Fred (Oxford University Press, 2010)
"Fred Feldman presents a study of the nature and value of happiness. Part One contains critical discussions of the main philosophical and psychological theories of happiness. Feldman presents arguments designed to show that each of these theories is problematic. Part Two contains his presentation and defense of his own theory of happiness, which is a form of attitudinal hedonism. On this view, a person's level of happiness may be identified with the extent to which he or she takes pleasure in things. Feldman shows that if we understand happiness as he proposes, it becomes reasonable to suppose that a person's well-being is determined by his or her level of happiness. This view has important implications not only for moral philosophy, but also for the emerging field of hedonic psychology. Part Three contains discussions of some interactions between the proposed theory of happiness and empirical research into happiness".